TNF activates calcium–nuclear factor of activated T cells (NFAT)c1 signaling pathways in human macrophages - Yarilina, Anna (National Academy of Sciences, 2011)
Acute activation of cells by tumor necrosis factor (TNF) has been well characterized, but little is known about later phases of TNF responses that are relevant for cells exposed to TNF for several days during inflammation. We found that prolonged exposure of human macrophages to TNF resulted in a wave of delayed but sustained activation of c-Jun and nuclear factor κB (NF-κB) proteins and of calcium oscillations that became apparent 1–3 d after TNF stimulation. These signaling events culminated in the induction and activation of the calcium-dependent transcription factor, nuclear factor of activated T cells (NFAT)c1, which mediated a gene expression program leading to cell fusion and osteoclast differentiation. TNF-induced NFATc1 activity primed macrophages for enhanced osteoclastogenesis in response to RANKL. High NFATc1 expression was apparent in synovial macrophages in a subset of patients with TNF-driven inflammatory arthritis. Thus, long-term exposure to TNF activates calcium-dependent signaling and an NFATc1-mediated gene activation program important for cell fusion and osteoclastogenesis. These findings identify a signaling pathway activated by TNF that is important for myeloid cell differentiation and suggest a role for TNF-induced calcium and NFAT signaling in chronic inflammation and associated bone resorption.